Is Keynesianism Institutionalist?: An Irreverent Overview of the History of Money from the Beginning of the Beginning to the Present - L. Randall Wray (Levy Economics Institute of Bard College, 1998)
This paper poses that the one commonality between institutionalist thought and Keynesianism (as presented in his General Theory) was money. Tracing the origins and uses of money, the myth of the development of money as a medium of exchange is dispelled and replaced with money used as evidence of debt, specifically, government debt. This paper was presented as the Presidential Address to the 1998 Association for Institutionalist Thought conference. As such, the paper should be taken in the same spirit as the [in]famous neoclassical Robinson Crusoe story, or Paul Samuelson's story of the evolution of money. The only significant change that has been made is to add several endnotes that will make some of the references more clear; this might make the piece more accessible for students.
Keywords: 330